Bioelectrochemistry–An Electrifying Experience Over 70 Years. Issue 21 (24th June 2019) - Bollella, Paolo; Santoro, Carlo; Cristiani, Pierangela; Atanassov, Plamen
Abstract: Professor Lo Gunnar Otto Gorton (Department of Analytical Chemistry/Biochemistry and Structural Biology, Lund University, Sweden) was born on 29 July 1949, and he will turn 70 years old this summer. This Special Collection on Bioelectrochemistry is dedicated to Lo on this landmark occasion. This preface gives some personal insights into Lo′s career beyond the traditional academic perspective. Abstract : Forever young : Professor Lo Gunnar Otto Gorton (Department of Analytical Chemistry/Biochemistry and Structural Biology, Lund University, Sweden) was born on 29 July 1949, and he will turn 70 years old this summer. This Special Collection on Bioelectrochemistry is dedicated to Lo on this landmark occasion. This preface gives some personal insights into Lo′s career beyond the traditional academic perspective.